Conectores Composite Dowels aplicados a pilares mistos de seção tubular de aço esbelta - Lucas Ribeiro dos Santos (2021)
The objective of this study is to evaluate the application of Composite Dowels connectors when used as load introduction devices in concrete-filled steel columns (CFSC), in which the circular tubular sections have a high local slenderness ratio, named in this work, as slender sections composite columns. Although other Composite Dowels connectors geometries were evaluated, such as Clothoid-Shaped and Puzzle-Shaped, relevance was given to Crestbond connector, which is a Brazilian technology. Experimental, numerical, and analytical analyzes were carried out to achieve the proposed objective. The experimental analysis was carried out in two steps, the first with experimental models of single connection with Crestbond connectors applied to slender sections composite columns and a concrete column representing a limit situation of profile with high local slenderness ratio, and the second, with experimental models of two connections with Clothoid-Shaped and Puzzle-Shaped connectors. With the experimental results it was possible to evaluate the behavior of connectors in relation to stiffness, ductility, and failure modes parameters. The numerical models were developed in the finite element program ABAQUS. The numerical parameters used in the simulation were the same applied in similar studies for compact section composite columns, making it possible to include in the parametric study, in addition to slender section models, compact and noncompact section models. With the parametric analysis results, it was observed in the composite columns that the failure was mainly related to the connector steel dowel. In the concrete columns, in addition to the steel dowel failure, pry-out and shearing concrete failures were observed. Given the limitations observed in the existing formulations, new formulations were proposed to calculate the resistant capacity of connectors applied to composite columns. The proposed formulations were evaluated for compact, noncompact and slender sections composite columns, and showed good agreement with parametric analysis results. In the end, the formulations were adjusted to the characteristic and design levels for application in steel and concrete composite structures projects.